Sprachliches Wissen zwischen Lexikon und Grammatik - Holler, Anke (Jahrbuch des Instituts für Deutsche Sprache, 2011)
This volume presents the current linguistic debate on the relationship between lexicon and grammar and on the status of constructions. It makes reference to investigations of phenomena relating to valence, argument structure, diatheses, collocations and phrasemes. Starting from different positions within linguistic theory, thecontributions also reflect the empirical methodologies currently applied to substantiate basic positions in linguistic theory.